Teachers' Perspectives on Students' Challenges in Understanding Arabic Metaphors: A Qualitative Study in Government-Aided Islamic Religious Schools in Malaysia - Nur Hidayah Mohd Yusoff; Lily Hanefarezan Asbulan; Suhaila Zailani Hj Ahmad (Ijaz Arabi Journal of Arabic Learning, 2026)
This study aims to explore the challenges faced by students in understanding the concept of isti’arah, which is one of the important elements in the subject of Balaghah. In addition, this study also assesses the level of effectiveness of the teaching approach currently practiced in religious education institutions under the management of the Federal Territory Islamic Religious Council (MAIWP). The approach of this study was qualitative, using a semi-structured interview method involving five Form Six students from two selected religious secondary schools who implemented the Early Curriculum at the STAM level. The data obtained was analyzed using a thematic approach to identify patterns, key issues, and suggestions for improvement submitted by students. The results of the study showed that students faced various challenges such as confusion in distinguishing between literal and figurative meanings, difficulty in understanding Balaghah's technical terms, as well as the absence of effective visual aids. In addition, the teaching method that is too teacher-centered and theory-oriented is also a factor in low and passive student involvement. Students suggest that learning resources be renewed with more interactive, engaging, and contextual approaches such as the use of animation, digital mind maps, virtual reality (VR) technology, as well as visual materials sourced from modern media and contemporary literary works. Based on these findings, this study proposes the development of a technology-based instructional learning model that emphasizes elements of visualization, interactivity, and application of real-world contexts. Overall, this study contributes to efforts to empower the pedagogy of Balaghah to be more innovative, student-centric, and in line with the needs of Islamic education in the digital era and the 21st century.